2022
DOI: 10.21053/ceo.2021.00654
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guideline: Nasal Irrigation for Chronic Rhinosinusitis in Adults

Abstract: The Korean Society of Otorhinolaryngology-Head and Neck Surgery and Korean Rhinologic Society appointed a guideline development group (GDG) to establish a clinical practice guideline, and the GDG developed a guideline for nasal irrigation for adult patients with chronic rhinosinusitis (CRS). The guideline focuses on knowledge gaps, practice variations, and clinical concerns associated with nasal irrigation. Nasal irrigation has been recommended as the first-line treatment for CRS in various guidelines, and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 134 publications
0
9
0
Order By: Relevance
“…A small proportion of ENT interviewees declared that in case of side effects such as dryness and bleeding or if the patient is intolerant to the use of nasal spray, they propose a nasal douche with diluted local corticosteroids. If, finally, side effects persist, discontinuation of treatment should be considered [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small proportion of ENT interviewees declared that in case of side effects such as dryness and bleeding or if the patient is intolerant to the use of nasal spray, they propose a nasal douche with diluted local corticosteroids. If, finally, side effects persist, discontinuation of treatment should be considered [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of nasal irrigation is influenced by factors such as the position of the head during irrigation, the volume of irrigation, and any nasal surgery related to the nasal cavity ( 36 ). As such, further evidence is necessary to select suitable irrigation methods, and determine the frequency and duration of their use ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertonic saline may also trigger the release of histamine, increasing nasal reactivity and secretion, which can ultimately decrease nasal airway capacity ( 41 ). Previous research has shown that nasal irrigation solutions at temperatures between 20–40 ℃ is considered safe and effective ( 37 ). However, more research needs to be conducted to determine the correlation between the appropriate temperature and the efficacy of nasal irrigation ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic rhinosinusitis (CRS) is characterized by persistent inflammation of the sinus mucosa, which results in nasal congestion, postnasal drip, facial pressure, and decreased olfactory function [ 1 , 2 ]. Furthermore, it leads to chronic pain, depression, and social dysfunction, which impair quality of life [ 3 ].…”
Section: Introductionmentioning
confidence: 99%